2015
DOI: 10.1016/j.jjcc.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Current concept of transcatheter closure of atrial septal defect in adults

Abstract: After the introduction of catheter intervention for atrial septal defect (ASD) in the pediatric population, therapeutic advantages of this less invasive procedure were focused on adult through geriatric populations. The most valuable clinical benefits of this procedure are the significant improvement of symptoms and daily activities, which result from the closure of left to right shunt without thoracotomy and cardiopulmonary bypass surgery. These benefits contribute to increase the number of adult patients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 36 publications
(54 reference statements)
2
49
1
1
Order By: Relevance
“…It is well known that morphological variations of ASD are frequent and appropriate patient selection for transcatheter ASD closure is crucial for successful procedure. 1 In our study four percentage of patients had more than one ASD. The presence of multiple defects of the inter-atrial septum have been reported between 5.3% to 7.3% of patients with ostium secundum ASD.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…It is well known that morphological variations of ASD are frequent and appropriate patient selection for transcatheter ASD closure is crucial for successful procedure. 1 In our study four percentage of patients had more than one ASD. The presence of multiple defects of the inter-atrial septum have been reported between 5.3% to 7.3% of patients with ostium secundum ASD.…”
Section: Discussionsupporting
confidence: 44%
“…1 Morphological variations of secundum-type ASD are common and their recognition is crucial for selection of patients suitability for percutaneous closure. 2 Transesophageal echocardiogram (TEE) remains the gold standard for ASD closure.…”
Section: Introductionmentioning
confidence: 99%
“…This is because a possible increase in left-toright shunt due to a reduction in pulmonary artery resistance might increase left ventricular inflow, leading to left ventricular heart failure due to masked left ventricular restriction [7] at the time of ASD closure. In this case, ASD closure with an ASO was safely performed without sure was greater than 70% of systemic pressure [8]. The pulmonary hypertension-specific medications that we administered are reportedly effective even in high-risk patients during long-term follow-up [8].…”
Section: Discussionmentioning
confidence: 78%
“…Transcatheter closure of an atrial septal defect (ASD) with different occluder systems yields excellent longterm results [1][2][3][4][5][6]. Embolisation of occluders occurs in about 2% [7].…”
Section: Introductionmentioning
confidence: 99%